The Correlation of Students’ Vocabulary Mastery and Translation Accuracy in Narrative Text - Nurfadhila, Putri; Intan, Nur; Sitti Maryam Hamid; Ratu Yulianti Natsir (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
The aim of this research is to examine the extent to which students' vocabulary mastery is related to the accuracy of their translation in the narrative text